Determinants of biosecurity practices in French duck farms after a H5N8 Highly Pathogenic Avian Influenza epidemic: The effect of farmer knowledge, attitudes and personality traits. Issue 1 (20th January 2020) - Delpont, Mattias; Racicot, Manon; Durivage, André; Fornili, Lucie; Guerin, Jean‐Luc; Vaillancourt, Jean‐Pierre; Paul, Mathilde C.
Abstract: Biosecurity is crucial for infectious disease prevention, more importantly in the absence of vaccination. The need for improving the implementation of biosecurity practices was highlighted in French duck farms following the 2016–2017 H5N8 Highly Pathogenic Avian Influenza (HPAI) epidemic. Farmers have multiple reasons for not implementing biosecurity practices: external (time, money) and internal (socio‐psychological). The purpose of this study was to determine how sets of socio‐psychological factors (i.e. knowledge on biosecurity and avian influenza transmission, attitudes, personality traits, social background) affect the adoption of on‐farm biosecurity practices. Biosecurity practices and socio‐psychological determinants were assessed during 127 duck farm visits, in South West France, using both questionnaires and on‐farm observations. Factorial analysis of mixed data (FAMD) and hierarchical clustering analysis (HCA) identified three groups of farmers with different socio‐psychological profiles: the first group was characterized by minimal knowledge, negative attitudes towards biosecurity, little social pressure and a low level of conscientiousness. The second group was characterized by more extensive experience in poultry production, higher stress and social pressure. The third group was characterized by less experience in poultry production, better knowledge and positive attitudes towards biosecurity, increased self‐confidence and orientation towards action. The first group had a significantly lower adoption of biosecurity measures than the two other groups. A better understanding of the factors involved in farmers' decision‐making could improve the efficiency of interventions aiming at improving and maintaining the level of on‐farm biosecurity in the duck industry.